FUNCTIONS AND PEDAGOGICAL SYSTEM OF VALUES OF THE TEACHER'S ACTIVITY (EDUCATION IN THE 21ST CENTURY, 2023)
The system of pedagogical values of the teacher's activity is discussed in this article , it examines not only his professional knowledge and practical skills, but also the image of a person who forms a system of values in accordance with the development of the new generation.The 21st-century child is endowed with the power of his imagination, outlook and awareness. Therefore, it is necessary to use all this pedagogically correctly for the benefit of the child. This requires certain steps that will ensure the effectiveness of the process. In this case, the role of the teacher , who connects different times and generations, transmits and distributes both national and universal cultural values and forms the generation of the future, is great.A person whose goal is not only to transfer knowledge, but also to form the direction of self-development and development of the child's value system, helps him in building his own life and outlook, and also plays an active role in the life of the child.
Keywords: Keywords - Pedagogical value system, quality of education, professional abilities and skills, pedagogical tact, pedagogical mastery, personality formation, socialization, pedagogical culture.